Pengaruh Potensi Diri dan Status Sosial Ekonomi terhadap Minat Melanjutkan Studi ke Perguruan Tinggi pada Siswa SMK Tirta Sari Surya - Amalia Alfath Anugrah Putri; Christian Wiradendi Wolor (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
The purpose of this study is to find out whether the influence of self-potential, socioeconomic status on interest in continuing their studies to higher education in students of SMK Tirta Sari Surya. This study uses a quantitative approach with a survey method. Data collection was obtained by distributing questionnaires in the form of Google Forms. The data used in this study is primary data obtained from sources or first people. The population of this study consisted of 110 respondents in class XI MPLB at SMK Tirta Sari Surya. The sample used in this study was 86 people using the Slovin formula. The data collected through the questionnaire was measured using a Likert scale with a score of 1 to 5. The data analysis technique in this study uses a Structural Equation Model (SEM) based on Partial Least Square (PLS) with SmartPLS 4.0 software. The results of the study showed that self-potential had a positive and significant effect on students' interest in continuing their studies in SMK Tirta Sari Surya students, socioeconomic status had a positive and significant effect on students' interest in continuing their studies in SMK Tirta Sari Surya students, and self-potential and socioeconomic status had a partial or simultaneous effect on students' interest in continuing their studies in SMK Tirta Sari Surya students.